Research and Innovations in Products Quality Improvement of Short Rotation Woods for Industry 4.0 - Wayan Darmawan (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2018)
Juvenile portion of tree stem surrounding the pith is characterized by a progressive change in cell features and wood properties (Panshin and de Zeeuw 1980). In comparison with mature wood, juvenile wood is made of smaller and shorter fibers with thinner walls and larger microfibril angles, lower density, and lower strength properties (Clark et al. 2006; Gryc et al. 2011; Koubaa et al. 2005: Adamopoulus et al. 2007; Evans et al. 2000). It is well known that characteristics of juvenile wood contribute to undesirable solid wood properties. Juvenile wood is not substandard for products such as newsprint and quality printing paper (Zobel 1984). However, it may cause serious problems for quality products, especially veneer or solid wood products. This is due to its low bending strength and dimensional instability upon drying. Juvenile wood of black locust had on average significantly lower static bending strength (MOR, and MOE), dynamic strength, and toughness strength than the mature wood (Adamopoulus et al. 2007). One of the most serious problems in drying and utilization of young plantation grown conifers was warp in the form of twist, crook and bow (Kliger 2001; Johansson and Kliger 2002). One possible means to reduce the negative impact of juvenile wood is to select for an earlier transition age from juvenile to mature wood.